Mesh Editing with Gradient Field Manipulation - Yu, Yizhou; Zhou, Kun; Xu, Dong; Shi, Xiaohan; Bao, Hujun; Guo, Baining; Shum, Heung-Yeung (Association for Computing Machinery, Inc., 2004)
In this paper, we introduce a novel approach to mesh editing with the Poisson equation as the heoretical foundation. The most distinctive feature of this approach is that it modifies the original mesh geometry implicitly through gradient field manipulation. Our approach can produce desirable and pleasing results for both global and local editing operations, such as deformation, object merging, and smoothing. With the help from a few novel interactive tools, these operations can be performed conveniently with a small amount of user interaction. Our technique has three key components, a basic mesh solver based on the Poisson equation, a gradient field manipulation scheme using local transforms, and a generalized oundary condition representation based on local frames. Experimental results indicate that our framework can outperform previous related mesh editing techniques.